Targeted and Untargeted Metabolomics Profiling of Wheat Reveals Amino Acids Increase Resistance to Fusarium Head Blight - Zhao, Peiying; Gu, Shubo; Han, Chao; Lu, Yaru; Ma, Chunyang; Tian, Jichun; Bi, Jianjie; Deng, Zhiying; Wang, Qunqing; Xu, Qian (Frontiers in Plant Science, 2021)
Fusarium head blight (FHB), a notorious plant disease caused by Fusarium graminearum, which is severely harmful to the wheat production, resulting in a decline in grain quality and yield. In order to develop novel control strategies, metabolomics has been increasingly used to characterize more comprehensive profiles of the mechanisms of underlying plant-pathogen interactions. In this research, untargeted and targeted metabolomics were used to analyze the metabolite differences between two wheat varieties, the resistant genotype Sumai 3 and the susceptible genotype Shannong 20, after F. graminearum inoculation. The untargeted metabolomics results showed that differential amino acid metabolic pathways existed in Sumai 3 and Shannong 20 after F. graminearum infection. Also, some of the amino acid contents changed a lot in different cultivars when infected with F. graminearum. Exogenous application of amino acids and F. graminearum inoculation assay showed that Pro and Ala increased wheat resistance to FHB, while Cys aggravated the susceptibility. This study provides an initial insight into the metabolite differences of two wheat cultivars under the stress of F. graminearum. Moreover, the method of optimization metabolite extraction presents an effective and feasible strategy to explore the understanding of the mechanisms involved in the FHB resistance.